2016
DOI: 10.1016/j.jms.2016.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Microwave spectrum and structure of the 3,5-difluoropyridine⋯CO2 van der Waals complex

Abstract: The rotational spectrum of the weakly bound complex 3,5-difluoropyridine•••CO 2 has been observed using pulsed-nozzle Fourier transform microwave spectroscopy. Spectroscopic constants are reported for the parent and 13 CO 2 isotopologues. The data indicate a planar structure in which the nitrogen approaches the carbon of the CO 2 with either a C 2v or effectively C 2v geometry in the ground vibrational state. The N•••C van der Waals bond distance is 2.8245(16) Å and the oxygen•••ortho-hydrogen distance is 3.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…As previously discussed, for example, the diazine−water complexes have nonlinear hydrogen bonds, likely resulting from analogous secondary interactions. Moreover, the short van der Waals bond lengths and lack of internal rotation in the complexes py− CO 2 18 and 3,5-difluoropyrine−CO 2 19 have been attributed to the secondary hydrogen bonds between the CO 2 oxygens and ortho-hydrogens. In the py−HCCH complex, 13 the acetylene forms a hydrogen bond to the nitrogen, but tilts so as to bring its π electron density closer to one or the other of the orthohydrogens, producing complex internal dynamics similar to those observed here.…”
Section: ■ Discussionmentioning
confidence: 99%
“…As previously discussed, for example, the diazine−water complexes have nonlinear hydrogen bonds, likely resulting from analogous secondary interactions. Moreover, the short van der Waals bond lengths and lack of internal rotation in the complexes py− CO 2 18 and 3,5-difluoropyrine−CO 2 19 have been attributed to the secondary hydrogen bonds between the CO 2 oxygens and ortho-hydrogens. In the py−HCCH complex, 13 the acetylene forms a hydrogen bond to the nitrogen, but tilts so as to bring its π electron density closer to one or the other of the orthohydrogens, producing complex internal dynamics similar to those observed here.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In these complexes, the carbon atom interacts with the nitrogen atom of NCH and NH 3 at N–C distances of 2.998 and 2.9875 Å, respectively. More recently, the structures of the pyridine:CO 2 and 3,5-difluoropyridine:CO 2 complexes have been reported. , In both cases, the complexes have planar C 2 v symmetry, with N–C distances of 2.7977 and 2.8245 Å, respectively. It is interesting that the N–C distances in the pyridine complexes are shorter than they are in the complexes with NCH and NH 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The main goal here is to find a compound that is able to change the electronic distribution of CO 2 to make this very stable compound a little more reactive. In previous works, it has been shown that carbon dioxide is able to form complexes with phosphines, sulfur dioxide, pyridine derivatives, imidazole, and other heterocycles. , It has also been proved that CO 2 can form adducts with carbenes and frustrated Lewis pairs (FLPs), some of them including silicon and germanium as Lewis acid centers. …”
Section: Introductionmentioning
confidence: 99%